Analisis Pendapatan Asli Desa, Dana Desa, dan Alokasi Dana Desa, terhadap Belanja Desa di Desa Ngalupolo Tahun 2023 - Tobias Timba; Murfani Umar Djalo (Jurnal Syntax Admiration, 2024)
This study aims to analyze the influence of Village Original Income, Village Funds, and Village Fund Allocation on Village Expenditure in Ngalupolo Village. Using quantitative methods, this study involves secondary data from the 2017 Village Revenue and Expenditure Budget, which is collected through observation, interviews, documentation, and literature studies. The analysis techniques used include classical assumption tests, multiple linear regression analysis, and t and F tests to see the influence of independent variables individually and simultaneously. The results of the study show that Village Original Income has a significant effect on Village Expenditure, while Village Funds and Village Fund Allocation do not have a significant influence. In conclusion, an increase in Village Original Income can increase the allocation of village expenditure, but the optimization of Village Funds and Village Fund Allocation needs to be improved to support more effective village development.